The role and mechanisms of cordycepin in inhibiting cancer cells - Gong Yu; Jiahua Peng; Lu Li; Wenbin Yu; Bin He; Bin Xie (Brazilian Journal of Medical and Biological Research, 2024)
With the escalating incidence and mortality rates of cancer, there is an ever-growing emphasis on the research of anticancer drugs. Cordycepin, the primary nucleoside antibiotic isolated from Cordyceps militaris, has emerged as a remarkable agent for cancer prevention and treatment. Functioning as a natural targeted antitumor drug, cordycepin assumes an increasingly pivotal role in cancer therapy. This review elucidates the mechanisms of cordycepin in inhibiting tumor cell proliferation, inducing apoptosis, as well as its capabilities in suppressing angiogenesis and metastasis. Moreover, the immunomodulatory effects of cordycepin in cancer treatment are explored. Additionally, the current status, challenges, and future prospects of cordycepin application in clinical trials are briefly discussed. The objective is to provide a valuable reference for the utilization of cordycepin in cancer treatment.